Cross-validation of the ego dissolution scale: implications for studying psychedelics - Lynn, Steven Jay; McDonald, Charlie W.; Sleight, Fiona G.; Mattson, Richard E. (Frontiers in Neuroscience, 2023)
Introduction Ego dissolution, variously called Ego-Loss, self-loss, and ego disintegration, is a hallmark of psychedelic drug use. We cross-validated the 10-item Ego Dissolution Scale, which we developed to assess ego dissolution in everyday life, and we included comparator variables that expanded our original assessment of construct validity. Methods Undergraduate college student volunteers (N = 527) completed the measures online. Results We replicated the original two factor structure (i.e., subfactors: Ego-Loss and Unity/connectedness with others, the world, universe), and we determined that the total score (Cronbach’s α = 0.79) and subfactors (Ego-Loss = 78; Unity = 0.83) possessed adequate-to-good reliability and strong convergent validity (e.g., mindfulness, hallucination-predisposition, sleep variables, personality variables, positive/negative affect transliminality, dissociation/depersonalization), while neuroticism, social desirability did not correlate highly with ego dissolution. We identified distinct patterns of relations of measures associated with the Ego-Loss vs. Unity subfactors. Discussion We discuss the implications of the use of the EDS for studying everyday aspects of ego dissolution, the long-term effects of psychedelic use, and the value of using the scale in conjunction with measures of the acute effects of psychedelics.